Implementation of A Community Service Program to Enhance the Capacity of Durian SMES - Falah Fadhlurahman (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the empirical implementation of a participatory community service program designed to elevate the organizational, financial, digital, and product innovation capacities of a grassroot durian enterprise in Ponorogo, East Java. Operating within a highly volatile seasonal market, the micro business historically suffered from structural operational obscurity, unstructured financial mixing, restricted localized communication networks, and high dependency on raw crop lifecycles. Through systematic intervention methodologies, the project introduced formalized management hierarchies, institutionalized digital transactional gateways via Quick Response Code Indonesian Standard frameworks, optimized multi channel digital marketing, and established value added product diversification lines including vacuum sealed pancakes and extended shelf life ice cream. The qualitative empirical evaluation reveals that the simultaneous integration of internal accounting controls and structured external market responsiveness successfully insulated the enterprise from environmental resource shocks and localized supply disruptions. Ultimately, this strategic capacity enhancement transforms vulnerable informal fruit vendors into highly resilient market participants, offering a robust model for sustainable regional agri food entrepreneurship and community driven economic development within modern digital ecosystems.